Benzoin, a resin produced by Styrax trees in North Sumatra Province, Indonesia - García Fernandez, C. (Center for International Forestry Research, 2004)
Sumatran benzoin is a resin produced by Styrax trees, managed in forest gardens in the highlands of North Sumatra. The resin is used in incense, perfume and pharmaceutical preparations and as a flafouring agent. Trade with foreign countries has existed for over a millennium, first with China and later with Arab and Europe. The economic and cultural roles of benzoin have undergone major changes in the last few decades. Previously benzoin gardening was considered a high status activity which generated high incame and made farmer proud. Nowadays some villages have abandoned the practices as other more profitable cash crops have displaced benzoin as an income source. The younger generations perceives benzoin cultivation as a backward activity, preferring to work in their annual crop gardens or for wages. Nevertheless some farmers remain attached to benzoin as they recognize it as the product that gave life to their settlement and provided the means to educate generations of relatives. From a conservation point of fiew, benzoin management represents low-intensity disturbance of the ecosystem and allows the effective accumulation of a forest species while maintaining the forest environment.